Satu Rumah Satu Jumatik Untuk Meningkat Keterampilan Warga Perumahan Puri Angsa Asri 2 Dalam Pencegahan DBD Di Muaro Jambi - M. Ridwan; Oka Lesmana; Vinna Rahayu Ningsih (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2019)
ABSTRACT Dengue Hemorrhagic Fever (DHF) is still one of the public health problems that is still the concern of the government in Indonesia. The number of sufferers is increasing from time to time and eventually lead to Extraordinary Events. Various efforts continue to be done to solve the problem of DHF in Jambi City which is an endemic area of ​​DHF. Data from the Jambi Provincial Health Office, recorded in January 2016 there were 466 cases with 4 deaths (13.7 Incident / 100,000 population) spread in 10 districts / cities except Kerinci Regency. The highest number of cases occurred in Jambi City with an Incidence Rate of 40.4 / 100,000 population (237 cases and 2 deaths). During January 2019 alone, there were already 25 cases of DHF recorded in the Muaro Jambi District Health Office. The village of Pondok goose housing is a border area between Jambi City and Muaro Jambi. Many settlements inhabited by Unja students must of course also be a concern. Fogging is not the right solution in limiting dengue mosquitoes. Efforts to improve prevention skills 1 house 1 jumantik so that each house will be able to clean the environment from mosquito nests so that it is expected to solve the problem of dengue cases in the village of pondok pondok swan. Keywords : Jumantik, 1 House 1 Jumantik, DBD